Advancing public health through Spatial Data Infrastructures: a review of global practices, governance and policy recommendations - Victor Mayowa Adeleye; Patrick Ashinze; Teslim Okeoyo; Veronica El Nabbout; Emmanuel Chileshe Phiri; Gargi Gautam; Collins Chukwunonso Ezea; Alhazan Amir Adebayo; Halima Ali; Ekemode Oluwadamilola Monsurat (Discover Public Health)
Abstract Background Spatial Data Infrastructure (SDI) frameworks provide a foundation for the integration and sharing of geospatial data, essential for public health decision-making. Effective governance of SDIs plays a critical role in improving health outcomes through disease surveillance, resource allocation, and health equity. While well-established SDIs like INSPIRE (Europe), NSDI (USA), and ASDI (Australia) offer functional models, they still face challenges. In contrast, regions like Africa and Asia struggle with SDI development due to disparities in funding, regulatory compliance, and technological integration. Objectives This study evaluates the role of government-regulated SDIs in shaping public health outcomes, focusing on gaps in governance, accessibility, interoperability and policies guiding geospatial data in public health contexts. Methods A systematic search was conducted across Scopus, PubMed, and Google Scholar on May 30th, 2024, yielding 129 articles. After screening, 75 articles were excluded for being non-SDI specific, editorial, or abstract-only. Data extraction focused on SDI governance and public health outcomes, and thematic analysis was used to assess the impact on disease surveillance, healthcare access, and data sharing. Results Out of 127 articles obtained, 33 addressed technological aspects of SDIs, with only two specifically focusing on public health. No studies addressed SDI policies directly within the public health framework, highlighting a significant research gap. Conclusion The lack of SDI policy integration in designing its platform in a public health context underscores the need for targeted research. Improved governance, policy frameworks, and collaboration in regions like Africa and Asia are essential to developing SDIs that can enhance public health outcomes.